PENDUGAAN BEBERAPA PARAMETER DINAMIKA POPULASI IKAN LAYANG (Decapterus macrosoma, BLEEKER 1841) DI PERAIRAN TELUK BONE, SULAWESI SELATAN - Suwarni, Suwarni; Triesnati, Joeharnani; Umar, Moh. Tauhid; Nur, Muhammad; Hikmasari, Hikmasari (Hasanuddin University, 2015)
his research was conducted in November to December 2012 which aimed to estimate thepopulation dynamic of mackerel fish through their age-group, growth, mortality, and yield perrecruitment. Samples were taken from the waters of sub district of Panyula, in the district of EastTanete Riatang, in Bone Region. Age-group was measured using Bhattacharya method with thehelp of Fish Stock Assessment Tools II (FISAT II) software. Growth and natural mortality weremeasured by applying the equations of Von Bertalanffy and Empiris Pauly (respectively). Whereastotal mortality as well as yield per recruitment were estimated by applying Beverton and Holdequation; and catch mortality was estimated by applying the equation of Z=F+M. Results showedthe average total length of 849 mackarel fish that was 121-295 mm. They were divided into 4groups with 306.35 mm asymptotic length, 0,33 growth rate coefficient and theoritical age of 0.0294year. Natural mortality rate, total and catch mortality, and exploitation rate were 0.3672per year; 2,4358 per year, 2,0687 per year and 0.8493 (respectively). This indicated that an overcatch had occurred due to the higher catch mortality compared to the natural mortality as well asthe yield per recruitment, i.e. 0.0865 gram/recruitment. Keywords : Population dynamic, mackerel fish, Bone Strait.